SISTEM INFORMASI PENERIMAAN KAS PADA PUSAT PENGELOLAAN KOMPLEK KEMAYORAN (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2024)
This study aims to analyze the cash receipt information system at the Pusat Pengelolaan Komplek Kemayoran using a descriptive qualitative approach. Data collection techniques included interviews, observation, and documentation. The results indicate that the cash receipt system—encompassing information requirements, related documents, and accounting records—is functioning effectively. Every transaction is supported by valid documentation, which serves as the basis for recording through the commercial accounting system.